2012
DOI: 10.1371/journal.pone.0039986
|View full text |Cite
|
Sign up to set email alerts
|

HLA Associations in Classical Hodgkin Lymphoma: EBV Status Matters

Abstract: The pathogenesis of classical Hodgkin lymphoma (cHL) involves environmental and genetic factors. To explore the role of the human leukocyte antigen (HLA) genes, we performed a case-control genotyping study in 338 Dutch cHL patients using a PCR-based sequence-specific oligonucleotide probe (SSOP) hybridization approach. The allele frequencies were compared to HLA typings of more than 6,000 controls. The age of the cHL patients varied between 13 and 81 years with a median of 35 years. Nodular sclerosis subtype w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
72
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(81 citation statements)
references
References 33 publications
(56 reference statements)
9
72
0
Order By: Relevance
“…In addition, several other HLA class II SNPs are associated with cHL (15,45 Ã 07:01 allele (45). This is in line with HLA typing studies that showed that HLA-DRB1 Ã 07:01 is a protective allele for developing NS cHL (26,29,30). Two SNPs mapping to nonclassical HLA genes in the HLA region, that is, MHC class I polypeptiderelated sequence B (MICB) (6p21.33) and proline-rich transmembrane protein 1 (PRRT1) (6p21.32) are associated with cHL overall, NS cHL, or EBV À cHL (15,45,47).…”
Section: Genome-wide Association Studiessupporting
confidence: 78%
“…In addition, several other HLA class II SNPs are associated with cHL (15,45 Ã 07:01 allele (45). This is in line with HLA typing studies that showed that HLA-DRB1 Ã 07:01 is a protective allele for developing NS cHL (26,29,30). Two SNPs mapping to nonclassical HLA genes in the HLA region, that is, MHC class I polypeptiderelated sequence B (MICB) (6p21.33) and proline-rich transmembrane protein 1 (PRRT1) (6p21.32) are associated with cHL overall, NS cHL, or EBV À cHL (15,45,47).…”
Section: Genome-wide Association Studiessupporting
confidence: 78%
“…However, the impact of HLA class I on EBV latency antigen‐specific CD8 + T cell immunity has not been determined systematically. Interestingly, large epidemiological and genomewide association studies have consistently reported differential HLA class I susceptibility to EBV + cHL (Supporting information, Table S1) 14, 15, 16, 17. In western European populations, HLA‐A*01 and HLA‐B*37 are associated with increased susceptibility to EBV + cHL, while HLA‐A*02 is associated with protection 15, 16, 17.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Rheumatoid arthritis has been consistently associated with HL in adults, conferring an estimated 3.3-fold greater risk, 15 while associations between other autoimmune diseases and HL have been observed in adults as well. 16,17 In addition, genome-wide association 18 and other genetic studies 19 have identified variants in HLA genes linked to increased HL susceptibility.…”
mentioning
confidence: 99%
“…4,18,19 To our knowledge, no prior studies have examined risk by tumor EBV status in pediatric and adolescent HL, although the available data indicate such stratification is warranted.…”
mentioning
confidence: 99%